Application of double low dose combined low flow injection in coronary dual‐source coronary computed tomography angiography. - Tang, Zhenhua (Echocardiography, 2018)
Purpose: This study was aimed to explore the feasibility of lower tube voltage, low volumes of contrast medium, and low flow injection in prospective electrocardiogram (ECG)‐triggered high‐pitch dual‐source coronary computed tomography angiography (CCTA) for coronary artery imaging. Material and Methods: A total of 140 patients with body mass index (BMI) ranging from 18.5 to 24.3 kg/m2 and heart rate (HR) lower than 65 times/min underwent CCTA were divided randomly into two groups. The enhanced CT value and noise as well as signal‐to‐noise ratio (SNR) and contrast‐to‐noise ratio (CNR) were calculated. Coronary artery was evaluated by double‐blind method using a four‐point grading scale. Results: No significant differences were found in the average enhanced CT value, noise, SNR, and CNR of all segments between the two groups (P > .05). Meanwhile, effective radiation dosages in group A were markedly lower than those in group B (P < .01). Conclusion: The prospective ECG‐triggered high‐pitch dual‐source CCTA with low voltage, contrast medium, and flow rate injection using sinogram affirmed iterative reconstruction is feasible which can observably reduce radiation and obtain satisfactory images.